Using Augmented Reality technology to improve English language learning by identifying objects around us - Nafisah Endahati; Setia Wardani (Universitas Ahmad Dahlan, 2023)
Educators are expected to be aware of information technology development. However, many teachers have not integrated technology into teaching strategies. This research aims at developing English learning media by using Augmented Reality (AR) technology and analyzed its effectiveness in learning. The researchers employed Microsoft Solution Framework (MSF) tool to develop the media which consisted of requirement definition, and system & software design. The developed media was evaluated through tests to 30 seventh graders of junior high school. Interview and observation were conducted to know users’ learning needs. Data was obtained by distributing questionnaires and quantitatively analyzed. The results show; 1) AR-based English media has 12 markers which can be downloaded in the application menu. The application display consisted of pre-elemi nary, marker, information, and theory pages. The chapter theory included 8 chapters; 2) The mean score of enthusiasm by implementing AR-based media is 27.07, but the score of non-implementing AR-based learning media is 22.33. It can be scientifically stated that AR-based media is effective to increase students’ enthusiasm in learning English. The AR technology can potentially be utilized to generate English media in productive skills. Thus, further researchers should investigate the integration of English material and AR technology effectiveness in receptive language skills.